2018
DOI: 10.1016/j.celrep.2018.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Meg3 Non-coding RNA Expression Controls Imprinting by Preventing Transcriptional Upregulation in cis

Abstract: Although many long non-coding RNAs (lncRNAs) are imprinted, their roles often remain unknown. The Dlk1-Dio3 domain expresses the lncRNA Meg3 and multiple microRNAs and small nucleolar RNAs (snoRNAs) on the maternal chromosome and constitutes an epigenetic model for development. The domain's Dlk1 (Delta-like-1) gene encodes a ligand that inhibits Notch1 signaling and regulates diverse developmental processes. Using a hybrid embryonic stem cell (ESC) system, we find that Dlk1 becomes imprinted during neural diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(100 citation statements)
references
References 43 publications
(63 reference statements)
3
97
0
Order By: Relevance
“…To explore if the perturbation of the Dlk1-Meg3 sub-TAD structure leads to incorrect imprinted activation of the Dlk1 gene, we performed in vitro differentiation of our WT and Δsite2 hybrid (BJ1 and JB1) ESCs into neural progenitor cells (NPCs) with cortical identity. In this system, imprinted Dlk1 activation can be readily recapitulated (25,27). In vitro differentiated NPCs from our JB1 and BJ1 deletion ESC lines were developmentally comparable to WT NPCs ( fig.…”
Section: Ctcf Binding At the Meg3 Dmr Is Required For Allelic Sub-tadmentioning
confidence: 74%
See 3 more Smart Citations
“…To explore if the perturbation of the Dlk1-Meg3 sub-TAD structure leads to incorrect imprinted activation of the Dlk1 gene, we performed in vitro differentiation of our WT and Δsite2 hybrid (BJ1 and JB1) ESCs into neural progenitor cells (NPCs) with cortical identity. In this system, imprinted Dlk1 activation can be readily recapitulated (25,27). In vitro differentiated NPCs from our JB1 and BJ1 deletion ESC lines were developmentally comparable to WT NPCs ( fig.…”
Section: Ctcf Binding At the Meg3 Dmr Is Required For Allelic Sub-tadmentioning
confidence: 74%
“…Rather, at both imprinted domains, maternal allele-specific CTCF binding hijacks an existing TAD organisation that is formed between bi-allelic CTCF bound clusters. The resulting maternal chromosome-specific sub-TADs are already established in ESCs, before imprinted activation of protein-coding genes on the paternal alleles (25). These allele-specific sub-TADs may thus provide the 'instructive' or 'permissive' context for correct developmentally regulated imprinted gene expression during development (29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 Long noncoding RNA (lncRNA) is a class of RNAs with more than 200 nucleotides which have less protein-coding capacities, those molecules function as key regulators in cellular activities (such as the process of cell cycle, differentiation, and imprinting). [5][6][7][8][9] Recent studies have revealed that lncRNAs may hold crucial triggers of the development and progression of hematological malignancies. 10 In AML, the studies aiming at investigating the role of lncRNA are limited, while the findings are minimal yet intriguing.…”
Section: Introductionmentioning
confidence: 99%